Sorry for your loss : a novel - McVeigh, Georgia (Dutton, 2026)
"Meet Iris: a dark soul with a propensity for obsession, still reeling from a recent loss, who relies on a local grief group to keep her grounded and out of trouble. And now meet Jack: a cagey widower who shows up at a meeting one night and jolts both of them back to life. From the moment Jack first takes a shabby plastic chair in the circle, he is positively dashing. And Iris can't help but feel that fate has brought them together. But their chance encounter sends them racing through a series of hairpin twists where nothing is as it seems and no one plays by the rules. As Iris is drawn deeper into Jack's world, she begins to realize that her own deceptions may be no match--or possibly even the perfect match--for all the dirty secrets Jack has been hiding"-- Provided by publisher.